Colloidal semiconductor nanocrystals for light emission and photonic integration - Huan Liu; Dabin Lin; Puning Wang; Tingchao He; Rui Chen (Chip, 2024)
Solution-processed colloidal semiconductor nanocrystals (NCs) have become attractive materials for the development of optoelectronic and photonic devices due to their inexpensive synthesis and excellent optical properties. Recently, CdSe NCs with different dimensions and structures have achieved significant progress in photonic integrated circuits (PICs), including light generation (laser), guiding (waveguide), modulation, and detection on a chip. This article summarizes the development of CdSe NCs–based lasers and discusses the challenges and opportunities for the application of CdSe NCs in PICs. Firstly, an overview of the optical properties of CdSe-based NCs with different dimensions is presented, with emphasis on the amplified stimulated emission and laser properties. Then, the nanophotonic devices and PICs based on CdSe NCs are introduced and discussed. Finally, the prospects for PICs are addressed.